SIRCuit: Supporting the psychological wellbeing of athletes: What can coaches do? - Bissett, J. (2020)
There has recently been an increasing number of athletes bravely coming forward to share their stories about the psychological distress and associated mental health challenges they experienced during their athletic careers (e.g., Michael Phelps, Gracie Gold, and Demar Derozan). Athletes are not immune to experiencing psychological distress and rates of mental illness among athletes are comparable to their non-athlete peers (Rice et al., 2016). Research has long suggested that athletes participating in sport, particularly at competitive and elite levels, may be at-risk for experiencing psychological distress and associated mental disturbance because of the various sport-specific stressors they may face, such as sustaining athletic injury, conflict with teammates, and pressures to achieve athletic success (Sudano, Miles, & Collins, 2017), as well as more personal life stressors, such as challenges with their sexuality (Kroshus & Davoren, 2016). In response to these stressors, athletes may suffer from impaired mental health including anxiety, depression, disordered eating, suicidal ideation, and alcohol or substance dependency (Rice et al., 2016).